2012
DOI: 10.1113/jphysiol.2012.231464
|View full text |Cite
|
Sign up to set email alerts
|

Preinspiratory calcium rise in putative pre‐Bötzinger complex astrocytes

Abstract: Key points• Autonomic respiratory rhythm is essential to maintain lives and is generated in the lower brainstem. The ventrolateral medullary region, called the pre-Bötzinger complex (preBötC), is the kernel for respiratory rhythm generation. Despite previous extensive studies focusing on neurons, the mechanism of how respiratory rhythm is generated has not been fully understood.• Here we show that non-neuronal glial cells (a subset of putative astrocytes) in the preBötC are periodically activated preceding ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 64 publications
11
66
0
Order By: Relevance
“…Under control conditions, astrocytes displayed a low oscillating frequency (1.1 ± 0.5 cycles/min in the preBö tC (n = 22 slices) vs. 1.1 ± 0.4 cycles/min in the pFRG/RTN (n = 19 slices); difference not statistically significant), similar to that described previously for active astrocytes (Grass et al, 2004;Schnell et al, 2011;Okada et al, 2012;Oku et al, 2016). The frequency displayed by the .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Under control conditions, astrocytes displayed a low oscillating frequency (1.1 ± 0.5 cycles/min in the preBö tC (n = 22 slices) vs. 1.1 ± 0.4 cycles/min in the pFRG/RTN (n = 19 slices); difference not statistically significant), similar to that described previously for active astrocytes (Grass et al, 2004;Schnell et al, 2011;Okada et al, 2012;Oku et al, 2016). The frequency displayed by the .…”
Section: Resultssupporting
confidence: 81%
“…It has also become evident that astrocytes are involved in respiratory behavior. The preBö tzinger Complex (preBö tC), a brainstem respiratory center (Grass et al, 2004), contain electrically active astrocytes, that exhibit rhythmic calcium (Ca 2+ ) oscillations associated with the respiratory-related neuronal rhythm (Schnell et al, 2011;Okada et al, 2012). Further, brainstem astrocytes respond to changes in blood gas levels (Angelova et al, 2015), especially in the chemosensitive region the parafacial respiratory group/retrotrapezoid nucleus (pFRG/RTN) (Huckstepp et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Fellin 2009). It has been proposed that astrocytes in the respiratory network may contribute to the characteristic of inspiratory activity (Hulsmann et al, 2000;Schnell et al, 2011;Okada et al, 2012;Oku et al, 2016) and play a crucial role in central chemoreception within the RTN (Gourine et al, 2010;Guyenet et al, 2016). The finding that ozone-induced pulmonary inflammation results in a specific activation of vagal afferents that induces astroglial cellular alterations in the NTS (Chounlamountry et al, 2015 also for further Refs.)…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…In most instances, the potential contribution of astrocytes, the most abundant type of cells in the brain, is largely ignored. Only in respiration has it been shown that astrocytes play a significant role by detecting pH changes in the blood and modulating neuronal firing in return 6,7 . Several ionic conductances endow neurons with rhythmogenic abilities.…”
Section: Introductionmentioning
confidence: 99%